The role of the tutor in supporting online engagement in higher education - O'Hare, Sheena (Curtin University, 2014)
In order to generate insights into the role of an online tutor in supporting student learning, this thesis studied the online interactions of four tutors who were teaching four separate groups of first-year undergraduate pre-service teachers. The study used focus group interviews, analysis of online transcripts and individual interviews. Several recommendations are made that provide university educators with new insights into ways to support online teaching and learning.